Sex differences in heritability of ischemic stroke: a systematic review and meta-analysis. - Touzé, E; Rothwell, P (2008)
BACKGROUND AND PURPOSE: Using data from Oxfordshire, UK, we recently showed that women are more likely than men to have a family history of stroke in female versus male first degree relatives. To test the generalizability of this finding, we did a comprehensive systematic review of all available published and unpublished data. METHODS: Studies were included in the present review if they reported the frequency of family history of stroke in relation to sex of parent or proband. Where necessary, we contacted authors of studies to obtain unpublished data. Data from the Oxford Vascular Study (OXVASC) and 3 other Oxford cohorts (1925 patients) were secondarily pooled with the data from other studies. RESULTS: We obtained data from 18 studies (7941 patients), including unpublished data from 7 studies. Female probands were slightly more likely to have a parental history of stroke than male probands (pooled OR=1.15; 95% CI: 1.03 to 1.29; P((sig))=0.028; P((het))=0.45). Maternal history of stroke was more common than paternal history (pooled OR=1.25; 1.15 to 1.37; P((sig))<0.00001; P((het))=0.12). However, the maternal excess was only present in female probands (pooled OR=1.47; 1.27 to 1.70; P((sig))<0.00001; P((het))=0.11). In contrast, male probands were no more likely to have maternal than paternal history of stroke (pooled OR=1.02; 0.88 to 1.17, P((sig))=0.43; P((het))=0.09). CONCLUSIONS: Women with stroke are more likely than men to have a parental history of stroke, which is accounted for by an excess maternal history of stroke. This finding could be explained by sex-specific genetic, epigenetic, or nongenetic mechanisms.